2018
DOI: 10.1007/s12195-018-0547-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Remodeling of Epitaxially Grown Collagen Fibrils

Abstract: Introduction— The extracellular matrix (ECM) in the tumor microenvironment contains high densities of collagen that are highly aligned, resulting in directional migration called contact guidance that facilitates efficient migration out of the tumor. Cancer cells can remodel the ECM through traction force controlled by myosin contractility or proteolytic activity controlled by matrix metalloproteinase (MMP) activity, leading to either enhanced or diminished contact guidance. Methods— Recently, we have leverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Therefore, in patients with CRC, changes in the remodeling and expression of different collagens should be comprehensively analyzed at different stages of tumor progression. Matrix collagen remodeling is largely regulated by the LOX and MMP family (50). The present study revealed that the expression of LOXL2, MMP-1, MMP-2, MMP-7 and MMP-9 at the tumor invasion front was significantly higher in the metastatic group than in the non-metastatic and normal groups.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Therefore, in patients with CRC, changes in the remodeling and expression of different collagens should be comprehensively analyzed at different stages of tumor progression. Matrix collagen remodeling is largely regulated by the LOX and MMP family (50). The present study revealed that the expression of LOXL2, MMP-1, MMP-2, MMP-7 and MMP-9 at the tumor invasion front was significantly higher in the metastatic group than in the non-metastatic and normal groups.…”
Section: Discussionmentioning
confidence: 46%
“…Matrix collagen remodeling is largely regulated by the LOX and MMP family ( 50 ). The present study revealed that the expression of LOXL2, MMP-1, MMP-2, MMP-7 and MMP-9 at the tumor invasion front was significantly higher in the metastatic group than in the non-metastatic and normal groups.…”
Section: Discussionmentioning
confidence: 99%
“…By adhering to them, myofibroblastic CAFs set this meshwork under strong tension and cause an increased interstitial pressure typical of solid tumors [ 434 , 435 ]. Conversely, ECM-cleaving MMPs, typically found during wound healing and in fibrotic processes, determine the turnover of the tumor stroma and reduce contact guidance by fibrillar matrix structures [ 436 ]. They are needed by the motile tumor cells to penetrate the dense and tensed collagen network of the TME and tumor collagenous capsule.…”
Section: Mmps and Tme: More Than A Hit-and-run Relationmentioning
confidence: 99%
“…Cells attached to the substrate could also participate in collagenase activity leading to collagen signal loss, however, such influence requisite significant cell contractility, which is highly unlikely given their limited adhesion with cellulose. [41,42] We subsequently treated the paper substrates with fluorinated alkyl silanes to improve stability during cell culture, which has been shown to delay biodegradation, in part, due to restricted permeation of moisture. [10] As expected, the dependence of collagen intensity with time diminished on treated paper (Figure 3c).…”
Section: Effect Of Surface Properties On Amount Of Adsorbed Collagenmentioning
confidence: 99%